NORTH-PARAHYBA PROVINCE TEACHING DAY-SCHOOL: formando professoras para o magistério primário (Revista Internacional de Formação de Professores, 2022)
This paper presents the results of a documental study in the realm of history about both implementation anditinerary of the Externato Normal (high school teachers' courses), from 1886-1892 in North-ParahybaProvince. The creation of this institution was one of the first steps taken by local public government, inorder to normatize teaching education and practice, with a view to instructional activities in primaryschools. The documental body used was composed of: speeches and reports by presidents of the ParaibanProvince, as well as public teaching managers' reports, addressed to Provincial presidents, Laws andRegulations of public teaching, besides local newspapers production of that time. Such an investigation hasproduced an amount of aspects related to teachers' training, and its process of institutionalization in Paraibansociety, during the second half of the XIX century. Thus, it contributes to new challenges and knowledgeincrease of Brazilian educational history, specifically of progression and regression in teachers' education.
Keywords: Teachers' education. Primary teaching. High school teachers' courses.